Competitive analysis of performance of strongest junior and senior cross-country skiers - Novikova, N. B.; Ivanova, I. G.; Kotelevskaya, N. B.; Golovachev, A. I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to profile and analyze the dynamics of competitive progress of the national and foreign elite cross-country skiers in the international events in the youth and senior age.